ANÁLISE DOS FORAMINÍFEROS RECENTES DA PLATAFORMA CONTINENTAL DE PERNAMBUCO, NE-BRASIL - Azevedo, Emanoel Marcos Medeiros de (2017)
The continental shelf of Pernambuco presents reduced width, shallow depth, gentle slope, relatively warm waters, high salinity and sedimentary cover composed by sediments terrigenous and biogenics. Among the biogenic sediments, the foraminiferal has importance for studies paleoceanographic and paleoecological, because they are predominantly marine and sensitive environmental changes (physical and chemical) and biotic that control about distribution biogeographical and bathymetric. The objective of this work was to know, identify and describe the foraminifera, their different morphogroups, and the taphonomic processes of the depositional environment to which they were incorporated and reworked by the processes of sedimentary dynamics of the continental shelf of Pernambuco. The samples used were collected on the continental shelf of Pernambuco, through a van-veen sampler at depths ranging from 13m to 32m. We analyzed 18 samples, which were washed to the according standard protocol for study of foraminiferal. After washing, 10g quarteted sediments were analyzed and a minimum of 300 individuals per sample. It was identified 22 genera of foraminiferal, of these 21 benthic and 1 planktonic. The most frequent genera were Archaias spp. (36.5%); Quinqueloculina spp. (21.1%) and Amphistegina spp. (16.2%), among others. In relation to the degree of preservation (72.3%) and staining (92.9%), these presented changes in their shells (fragmented, dissolved, encrusted, brown, yellow and mottled). These taphonomic data (preservation and coloration) show an ancient fauna (relict) and quite representative. The foraminiferal microfauna presented in this work is typical of shallow tropical waters, warm and of good luminosity, Besides being predominantly of internal to medium platform.